Teaching strategies to enhance the learning of the listening comprehension in english classes for students in their third educational academic year at Unidad Educativa Bilingüe Steiner, Academic year 2013-2014 - Auria Jiménez, Narcisa Elizabeth (2013)
This research project studies the different problems the student faces when he is practicing or working with Listening – Comprehension activities in the English class due to the lack of training in this skill. This kind of issue is connected to the weak teaching strategies that the teacher has used in order to develop listening – comprehension activities in English. This problem also deals with the selection of wrong material or the lack of appropriate resources in the English class in order to provide the student with the correct and most adequate strategies to develop listening – comprehension activities in a natural and meaningful way. At the same time this research project presents the most adequate teaching strategies in order to enhance listening- comprehension problems based on the Constructivism theory with the purpose of developing and work successful results in the students. It is advisable to create and implement interesting and significant activities that can explore and analyze how the metacognitive strategies with worthwhile listening activities can help the students to have a better development in this important skill in real life situations, so that the student will be able to act naturally at the moment he has to decode spoken messages….